Business Model Canvas and Strategies to Develop Biodiesel Industry of PT. XYZ in Order to Implement CPO Supporting Fund Policy - Aman Mustika; Rina Oktaviani; Sukardi Sukardi (Indonesian Journal of Business and Entrepreneurship (IJBE), 2017)
Biodiesel is considered as one of the alternative eco-friendly fuels. Besides, the government also issued policy related to biodiesel that is CPO Supporting Fund (CSF) Policy. The aim of the research is to identify Business model canvas (BMC) biodiesel industry in PT XYZ and to know the strategies to develop business from biodiesel industry in line with the CPO supporting fund policy. The analysis tool used in this research is BMC, SWOT and Quantitative Strategic Planning Matrix (QSPM). The research results in identifying BMC of PT XYZ is customer segment that the company serves in the form of domestic as well international customers. The value the company offers is biodiesel quality that is in accordance with SNI standard and the distribution is at the company’s cost; the relationship built with the customers is by communities and co-creation; the marketing network through stock exchanges and commodity exchanges; the revenue obtained from selling biodiesel and the price difference between biodiesel and solar from BPDPKS; the company’s resources are human resource, raw material resource, and financial resource; the main activities carried out by the company is CPO process to become biodiesel and sale; the company’s partners are GAPKI, BPDPKS and APROBI; the cost structure is operational cost, workers’ salary, and CPO levy fund. Furthermore, the strategy to develop biodiesel industry in line with the rapid increase of competitiveness is to increase the biodiesel production capacity and communication improvement and CRM to improve customers’ service.Keywords: biodiesel, CPO supporting fund (CSF), levy fund, vegetable oil (BBN), business model canvas (BMC)